Method and system for analyzing energy storage of nanocomposite in high-performance supercapacitor

The GO/Cu1-xSrxCr2O4 nanocomposite was synthesized and calcined by the precipitation method, and the existing supercapacitor electrode materials were solved, and the high-performance and environmentally friendly energy storage effect was achieved.

CN119314812APending Publication Date: 2025-01-14YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422513.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing supercapacitor electrode materials have limited conductivity, complex and expensive synthesis processes, reduced energy storage efficiency due to lower specific capacitance, poor cycle stability in multiple charge and discharge cycles, and toxic substances or unsustainable production methods Related environmental issues.

Method used

GO/Cu1-xSrxCr2O4 nanocomposite was synthesized by precipitation method and calcined at 70°C for 2 hours. A high-performance supercapacitor nanoelectrode material was developed, using the synergistic effect of GO/Cu1-xSrxCr2O4 doping on graphene sheets. Improve electrochemical properties and conductivity.

Benefits of technology

It significantly improves the electrochemical performance and cycle stability of supercapacitors, improves energy storage efficiency, simplifies synthesis processes, reduces production costs, and is environmentally friendly to support sustainable energy storage solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314812A_ABST
    Figure CN119314812A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemistry, and discloses an energy storage analysis method and system of a GO / Cu1-xSrxCr2O4 nano composite material in a high-performance supercapacitor, GO / Cu1-xSrxCr2O4 nano particles are successfully synthesized through a simple precipitation route and calcination at 70 DEG C for 2 hours, and a high-performance supercapacitor nano electrode material is formed. Electrochemical impedance spectroscopy analysis shows that compared with GO and CuCr2O4, the GO / Cu (1-x) SrxCr2O4 nano composite material has relatively low charge transfer resistance (Rct) of 1.29 omega, which indicates that the GO / Cu (1-x) SrxCr2O4 nano composite material has higher conductivity. In a 1M KOH electrolyte, the GO / Cu (1-x) SrxCr2O4 nano composite material has the maximum specific capacitance of 1935.8 F / g at the scanning rate of 3mV / s, and the maximum specific capacitance is obviously higher than that of GO (480.190 F / g) which is independently used. The potential of the GO / Cu1-xSrxCr2O4 nano composite material serving as an efficient supercapacitor electrode material is shown, and enhanced capacitance and conductivity are shown through the synergistic effect among the components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology and particularly relates to a GO / Cu 1-x Sr x Cr2O4 nanocomposites for energy storage in high performance supercapacitors. Background Art

[0002] Nanocrystalline transition metal oxides (NTMOs), such as copper chromates (e.g., CuCr2O4), are well known for their catalytic, optical, magnetic, and electrical properties and play an important role in various scientific and engineering applications. These materials are widely used as catalysts in industrial processes, such as hydrogenation, oxidation, and dehydrogenation reactions, due to their strong commercial viability and versatile chemical properties. The performance and properties of NTMOs depend largely on the synthesis techniques, which affect factors such as chemical composition, crystal structure, phase purity, particle size, and particle size distribution. Achieving precise morphological control is crucial to improve catalytic efficiency, which has prompted the exploration of synthetic methods such as hydrothermal, microwave, precipitation, inverse microemulsion, and sol-gel methods. Among these methods, sol-gel methods stand out due to their ability to produce monodisperse nanoparticles with controlled size and uniform distribution, thereby promoting superior nanostructural properties and enhanced catalytic activity. Meanwhile, since the isolation of graphene in 2004, two-dimensional nanomaterials such as graphene have gained great attention due to their sp 2 Graphene has attracted great attention due to its unique structure of bonded carbon atoms arranged in a honeycomb lattice. The excellent mechanical, electrical and thermal properties of graphene have stimulated research in various fields, including energy storage and electrochemical applications. These materials play an important role in solving challenges such as ion diffusion resistance in supercapacitors, thereby improving their efficiency and performance.

[0003] The current embodiment closest to the present invention involves the synthesis of GO / Cu for high performance supercapacitor electrodes. 1- x Sr x Cr2O4 nanoparticles. This method uses a precipitation method and then calcination at a relatively low temperature (70°C, 2 hours) to prepare GO / Cu 1-x Sr x Cr2O4 nanocomposites. This synthesis method ensures that GO / Cu 1-x Sr x Cr2O4 was effectively integrated onto graphene oxide sheets, optimizing the electrochemical performance of the material for energy storage applications. The structural integrity and performance enhancement of the nanocomposite were verified by characterization techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). The specific capacitance of the electrode was evaluated using a three-electrode configuration system, showing that the GO, GO / Cu1-x Sr x The significant improvement brought by the synergistic effect between Cr2O4 and graphene. This implementation emphasizes the simplicity, economy and environmental protection in the synthesis process of NTMO, which is consistent with the overall goal of advancing energy storage technology through innovative electrode materials.

[0004] Two-dimensional nanomaterials, such as graphene, an allotrope of carbon, have attracted much attention due to their unique structure. 2 The bonded carbon atoms are arranged in a honeycomb lattice framework. Since graphene sheets were isolated in 2004, researchers have been actively exploring new applications that exploit graphene's chemical, optical, and electromagnetic properties. One area of ​​particular focus has been overcoming the resistance to electrolyte ion diffusion in electrochemical tests, taking advantage of graphene's unique physicochemical properties. Transition metal oxides are commonly used in energy storage and conversion materials, known for their cost-effectiveness and high stability. Copper-based materials, in particular, have demonstrated ultra-high capacitance values ​​of up to 3000Fg1.

[0005] Through the above analysis, the problems and defects of the prior art are as follows:

[0006] Existing supercapacitor electrode materials have several drawbacks that limit their widespread adoption in high-performance energy storage applications. These drawbacks include limited electrical conductivity, complex and expensive synthesis processes, low specific capacitance leading to reduced energy storage efficiency, poor cycling stability over multiple charge-discharge cycles, and environmental issues associated with toxic substances or unsustainable production methods. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a GO / Cu 1-x Sr x Analytical methods for energy storage in high performance supercapacitors using Cr2O4 nanocomposites.

[0008] The present invention is achieved by: a GO / Cu 1-x Sr x Cr2O4 nanocomposites for energy storage in high performance supercapacitors include:

[0009] Step 1: Synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites.

[0010] Step 2, calcining at 70°C for 2 hours to develop a high-performance supercapacitor nanoelectrode material.

[0011] Step 3, the maximum specific capacitance is measured in a three-electrode configuration system, showing that the GO / Cu1- x Sr x Capacitance properties of Cr2O4.

[0012] Further, the synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composite material approach.

[0013] (1) Synthesis of graphene oxide GO.

[0014] (2) GO / Cu 1-x Sr x Synthesis of Cr2O4 / graphene oxide GO nanocomposites.

[0015] Furthermore, the graphene oxide GO synthesis method.

[0016] First, 3 g of graphite powder, 23 ml of nitric acid, and 46 ml of concentrated sulfuric acid were mixed to synthesize graphene oxide GO; the mixture was stirred at room temperature for 40 minutes.

[0017] In an ice bath at 5°C, 9 g of potassium permanganate was added dropwise over 60 minutes while stirring continuously; the temperature was maintained at 38°C, stirring was continued for one hour, and 200 ml of deionized water was added dropwise; after the temperature was raised to 98°C, 30 ml of 35% concentration of hydrogen peroxide H2O2 was added, and the mixture turned bright yellow the next day; using a vacuum filtration device for cleaning, a solution of 200 ml of deionized water and 16.6 ml of concentrated hydrochloric acid was prepared until a neutral pH value was reached; after two hours of ultrasonic treatment, the produced GO was collected in a slurry form by centrifugation at a speed of 12,000 rpm for 40 minutes.

[0018] Finally, they were dried in vacuum at 60 °C for 48 h and then ground into homogeneous powder for further characterization.

[0019] Furthermore, the GO / Cu 1-x Sr x Synthesis method of Cr2O4 / graphene oxide GO nanocomposites.

[0020] 1 g of graphene oxide and 3 g of GO / Cu 1-x Sr x Cr2O4 / GO was dispersed in a mixed solution of 40 ml acetic acid and 20 ml ethylene glycol, and then ultrasonically treated at 60 °C for 1 h. The obtained GO and GO / Cu 1-x Sr xThe mixture of Cr2O4 nanoparticles was sonicated for 15 min at a ratio of 1:1 and then magnetically stirred at 85 °C for 1 h; after the mixture was cooled, it was washed several times with deionized water until neutral by centrifugation at 3000 rpm for 15 min and finally dried in a vacuum oven at 60 °C overnight.

[0021] Furthermore, the maximum specific capacitance is measured in a three-electrode configuration system.

[0022] 1) X-ray diffraction analysis.

[0023] 2) Scanning electron microscopy.

[0024] 3) Optical analysis.

[0025] 4) Electrochemical measurements.

[0026] Further, the X-ray diffraction analysis.

[0027] Powder X-ray diffraction (XRD) technology was used to determine the properties of graphene oxide GO, CuCr2O4 and GO / Cu 1-x Sr x Percent crystallinity, d-spacing, crystal structure, lattice constant, surface area, and grain size of Cr2O4 / graphene oxide nanocomposites.

[0028] Another object of the present invention is to provide a GO / Cu 1-x Sr x Cr2O4 nanocomposites in high performance supercapacitor energy storage analysis system includes:

[0029] Precipitation module for the synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites.

[0030] Calcination module, used to calcine at 70°C for 2 hours to develop a high-performance supercapacitor nanoelectrode material.

[0031] Measurement module for measuring the maximum specific capacitance in a three-electrode configuration system showing the incorporation of GO / Cu on graphene sheets 1-x Sr x Capacitance properties of Cr2O4.

[0032] Another object of the present invention is to provide a computer device, the computer device comprising a memory and a processor, the memory storing a computer program, and when the computer program is executed by the processor, the processor executes the GO / Cu 1-x Sr xSteps in the analytical method for Cr2O4 nanocomposites for energy storage in high performance supercapacitors.

[0033] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, wherein when the computer program is executed by a processor, the processor executes the GO / Cu 1-x Sr x Steps in the analytical method for Cr2O4 nanocomposites for energy storage in high performance supercapacitors.

[0034] Another object of the present invention is to provide an information data processing terminal, the information data processing terminal is used to implement the GO / Cu 1-x Sr x Analysis of Cr2O4 nanocomposites in high performance supercapacitor energy storage systems.

[0035] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0036] First, in the present invention, GO / Cu was synthesized by a simple precipitation method. 1-x Sr x The Cr2O4 nanoparticle composite was then calcined at 70 °C for 2 h to develop a high-performance supercapacitor nanoelectrode material. The maximum specific capacitance was measured in a three-electrode configuration system, showing the high specific capacitance due to the incorporation of GO / Cu on the graphene sheet. 1-x Sr x The novelty of the present invention lies in the simplicity of the synthesis process of the nanocomposite material and its excellent properties as a supercapacitor electrode for energy storage applications. 1-x Sr x Cr2O4 has been shown to effectively increase the interfacial electron transfer rate. This enhancement effect shows the maximum specific conductivity in alkaline media, thereby improving the electrochemical performance of supercapacitors. 1-x Sr x The synergistic effect of Cr2O4 and graphene in the nanocomposite helps to improve the overall conductivity, making it a valuable candidate for advanced energy storage applications.

[0037] Existing supercapacitor electrode materials have several drawbacks that limit their widespread adoption in high-performance energy storage applications. These drawbacks include limited electrical conductivity, complex and expensive synthesis processes, reduced energy storage efficiency due to low specific capacitance, poor cycling stability over multiple charge and discharge cycles, and environmental issues associated with toxic substances or unsustainable production methods.1-x Sr x Electrodes made of Cr2O4 nanocomposites have been developed to improve the performance of supercapacitors. This new electrode material combines GO / Cu 1- x Sr x Cr2O4 is combined with graphene oxide (GO) to significantly improve the electrochemical performance of the electrode by utilizing their respective excellent properties. 1-x Sr x Cr2O4 provides high specific capacitance and good stability, while the high conductivity and large surface area of ​​GO help to improve the electron transfer rate and the overall conductivity of the electrode. This synergistic effect not only improves the energy storage efficiency of supercapacitors, but also improves their cycle stability and environmental friendliness, making it a high-performance energy storage solution with great potential.

[0038] The proposed nanocomposites have promising applications in high-performance supercapacitors, providing a significant advancement in energy storage technology.

[0039] The novelty of the present invention lies in the simple synthesis process of the nanocomposite material, while having excellent properties as a supercapacitor electrode for energy storage applications.

[0040] This enhancement effect exhibits the maximum specific conductivity in alkaline medium (1 M KOH), thereby improving the electrochemical performance of the supercapacitor.

[0041] GO / Cu 1-x Sr x The synergistic effect of Cr2O4 and graphene in the nanocomposite helps to improve the overall conductivity, making it a valuable candidate for advanced energy storage applications.

[0042] In addition, the invention's simplified and cost-effective synthesis process facilitates scalable production while maintaining high performance standards. By providing higher specific capacitance and improved cycling stability, the nanocomposite addresses key limitations of existing materials.

[0043] Additionally, its environmentally friendly composition supports sustainable energy storage solutions, making it a promising advancement in the field of green energy production and storage technology.

[0044] The present invention successfully synthesized GO / Cu by a simple precipitation route and calcination at 70 °C for 2 h. 1-x Sr x Cr2O4 nanoparticles form high-performance supercapacitor nanoelectrode materials. Electrochemical impedance spectroscopy analysis shows that compared with GO and CuCr2O4, GO / Cu 1-x Sr xThe Cr2O4 nanocomposite has a lower charge transfer resistance (Rct) of 1.29Ω, indicating that it has higher conductivity. 1-x Sr x The Cr2O4 nanocomposite material has a maximum specific capacitance of 1935.8 F / g at a scan rate of 3 mV / s, which is significantly higher than GO (480.190 F / g) used alone. 1- x Sr x Cr2O4 nanocomposites have the potential as efficient supercapacitor electrode materials, exhibiting enhanced capacitance and conductivity properties through the synergistic effects between the components.

[0045] Second, the technical solution provided by the present invention has significant economic benefits and commercial value. 1- x Sr x Cr2O4 nanocomposites exhibit excellent electrochemical properties, such as higher specific capacitance and improved conductivity, facilitating the development of high-performance supercapacitors with improved energy storage efficiency and charge-discharge cycle performance. The synthesis method is simple and cost-effective, involving precipitation and low-temperature calcination processes, which reduces production costs and enables large-scale manufacturing, providing a competitive advantage in the market. Environmentally friendly materials and processes support sustainable production methods, in line with the growing demand for green energy solutions, enhancing the commercial appeal of the technology. High-performance supercapacitors developed using this nanocomposite can be applied in multiple industries, including renewable energy storage, electric vehicles, portable electronics, and grid energy storage, broadening market potential and increasing commercial opportunities. By addressing the limitations of existing supercapacitor materials, such as low conductivity, complex synthesis processes, and environmental issues, the invention has attracted the interest of industries seeking more efficient and sustainable energy storage solutions as a superior alternative. 1-x Sr x Patenting the synthesis methods and applications of Cr2O4 nanocomposites provides significant intellectual property value, leading to licensing opportunities, collaborations with other companies and research institutions, and generating additional revenue streams. The improved performance of supercapacitors contributes to more efficient energy storage systems, reduces energy losses, promotes sustainable development, is in line with global efforts to transition to renewable energy, and attracts financial support from governments and environmental organizations. Due to the increasing adoption of electric vehicles, renewable energy systems, and portable electronics, the demand for advanced energy storage solutions is also growing, presenting a lucrative market opportunity. The invention meets these needs with its improved performance and cost-effectiveness, placing it in a favorable position for market growth.

[0046] Third, the present invention solves the technical problems of the prior art.

[0047] 1. The performance of electrode materials is limited.

[0048] In existing supercapacitor technology, the performance of electrode materials directly determines the energy density and power density of the capacitor. Although traditional electrode materials such as activated carbon and metal oxides have certain electrochemical properties, their specific capacitance is limited and cannot meet the higher requirements of high-performance energy storage devices for energy density and charge and discharge rates.

[0049] 2. Material preparation is complex and costly.

[0050] The preparation process of many high-performance electrode materials is complicated and requires high temperature, high pressure or specific atmosphere conditions, which leads to high production costs and difficulty in large-scale application. At the same time, the poor uniformity and controllability of the materials also make their stability and repeatability insufficient in practical applications.

[0051] 3. Conductivity and stability issues of electrode materials.

[0052] Existing electrode materials are prone to electrochemical decay during long-term charge and discharge cycles, resulting in reduced capacitance performance. In addition, the insufficient conductivity of some materials limits their performance during rapid charge and discharge, and cannot meet the needs of high-frequency applications.

[0053] The technical solution and significant progress of the present invention.

[0054] 1. Development of high-performance electrode materials.

[0055] The present invention synthesizes GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composite material and calcined at 70℃ for 2 hours to develop a high-performance supercapacitor nanoelectrode material. 1-x Sr x Cr2O4 composite materials have higher specific capacitance and better electrochemical properties. The high surface area and good conductivity of this material make it perform well in energy storage and can significantly improve the energy density and power density of supercapacitors.

[0056] 2. Simplified material preparation process.

[0057] The present invention adopts a relatively simple precipitation method to prepare GO / Cu 1-x Sr xCr2O4 nanocomposite material is processed by moderate calcination temperature (70°C). This process not only reduces the cost and complexity of material preparation, but also ensures the uniformity and controllability of the material, making the material more practical and popularizable. Compared with high temperature and high pressure preparation technology, the present invention provides a more economical and easy-to-operate preparation method.

[0058] 3. Significantly improved material conductivity and stability.

[0059] GO / Cu 1-x Sr x The Cr2O4 nanocomposite material significantly improves the conductivity of the material by combining it with graphene oxide (GO), while enhancing its stability during charge and discharge cycles. The test results of the electrode material in a three-electrode configuration system show that the material maintains a high specific capacitance and good electrochemical stability during multiple charge and discharge cycles, effectively solving the performance degradation problem of existing materials during long-term use.

[0060] The present invention develops GO / Cu 1-x Sr x Cr2O4 nanocomposites have successfully solved the problems of limited performance, complex preparation and insufficient conductivity of existing supercapacitor electrode materials. Through simplified preparation processes and composite material design, this technology significantly improves the energy storage capacity and cycle stability of supercapacitors, which is an important technological advancement and provides a new solution for the application and promotion of high-performance energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 The GO / Cu provided in the embodiment of the present invention 1-x Sr x Flowchart of analytical methods for energy storage of Cr2O4 nanocomposites in high-performance supercapacitors.

[0062] Figure 2 The GO / Cu provided in the embodiment of the present invention 1-x Sr x Structural block diagram of Cr2O4 nanocomposite materials in high-performance supercapacitor energy storage analysis system.

[0063] Figure 3 The embodiments of the present invention provide (a) graphene oxide (GO), (b) chromium copper oxide (CuCr2O4), (c) GO / Cu 1-x Sr x X-ray diffraction peak pattern of Cr2O4 nanocomposite materials.

[0064] Figure 4The SEM micrographs provided in the embodiments of the present invention respectively show that (a) part is graphene oxide (GO), (b) part is chromium copper oxide (CuCr2O4), and (c) part is GO / Cu 1-x Sr x Figure 1. Cr2O4 nanocomposite material.

[0065] Figure 5 The GO / Cu provided in the embodiment of the present invention 1-x Sr x EDS results of Cr2O4 / graphene oxide nanocomposite materials.

[0066] Figure 6 The embodiments of the present invention provide (a) graphene oxide (GO) and (b) GO / Cu 1-x Sr x Raman spectrum of Cr2O4 nanocomposite.

[0067] Figure 7 The embodiments of the present invention provide (a) graphene oxide (GO) and (b) GO / Cu 1-x Sr x Photoluminescence spectrum of Cr2O4 nanocomposite.

[0068] Figure 8 The embodiments of the present invention provide (a) graphene oxide (GO), (b) chromium copper oxide (CuCr2O4), (c) GO / Cu 1-x Sr x Electrochemical impedance spectroscopy of Cr2O4 nanocomposites.

[0069] Fig. 9 (a) GO (b) GO / Cu provided in the embodiment of the present invention 1-x Sr x Cyclic voltammogram of Cr2O4 electrode and Randall-Sevik plot density plot in 1 M KOH.

[0070] Fig.10 The GO / Cu provided in the embodiment of the present invention 1-x Sr x GCD curves and Ragone plots of Cr2O4 nanocomposite-based nanoelectrodes. DETAILED DESCRIPTION

[0071] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0072] like Figure 1As shown, a GO / Cu 1-x Sr x The analytical method for energy storage of Cr2O4 nanocomposites in high performance supercapacitors includes the following steps:

[0073] S101, Synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites.

[0074] S102, calcined at 70 °C for 2 h, developed a high-performance supercapacitor nanoelectrode material.

[0075] S103, the maximum specific capacitance measured in a three-electrode configuration system, showing that GO / Cu doped on graphene sheets 1- x Sr x Capacitance properties of Cr2O4.

[0076] GO / Cu provided in the embodiment of the present invention 1-x Sr x The application of Cr2O4 nanocomposites in high-performance supercapacitor energy storage is achieved through a series of steps to achieve the synthesis and electrochemical performance evaluation of nanocomposites. First, in step S101, GO / Cu 1-x Sr x Cr2O4 nanoparticle composite materials. Precipitation method is a commonly used wet chemical synthesis method. By controlling the reaction conditions in the solution (such as pH value, temperature, reaction time, etc.), GO / Cu 1-x Sr x Cr2O4 nanoparticles are uniformly precipitated in the solution and combined with GO (graphene oxide) to form a composite material. This method can effectively control the size and distribution of nanoparticles and ensure the uniformity and stability of the material.

[0077] In step S102, the synthesized GO / Cu 1-x Sr x The Cr2O4 nanocomposite was calcined at 70°C for 2 hours. The calcination process helps to improve the crystallinity of the material and enhance the electrochemical properties of the material. By calcining at a moderate temperature, organic impurities and unreacted precursors in the material can be removed, while making the GO / Cu 1-x Sr x Cr2O4 nanoparticles are evenly distributed on the surface of GO. Calcination can also increase the conductivity and stability of the material, thereby developing a high-performance supercapacitor nanoelectrode material.

[0078] In step S103, the GO / Cu1-x Sr x The electrochemical properties of Cr2O4 nanocomposites were evaluated. The three-electrode system includes a working electrode, a reference electrode, and a counter electrode, which can accurately measure the electrochemical properties of electrode materials. The prepared composite material was used as a working electrode material to measure its capacitive performance in different voltage ranges. The experimental results show that the addition of GO / Cu 1-x Sr x After the addition of Cr2O4 nanoparticles, the specific capacitance of the electrode material was significantly improved, indicating that the material has excellent energy storage performance in supercapacitors.

[0079] Finally, through this series of steps, the present invention successfully developed a high-performance supercapacitor nanocomposite material, and verified the application potential of the material in energy storage through detailed electrochemical tests. This method not only simplifies the material preparation process, but also effectively improves the electrochemical performance of supercapacitors, providing new ideas and solutions for the development of efficient energy storage devices.

[0080] Synthesis of GO / Cu by precipitation method provided by the embodiment of the present invention 1-x Sr x Cr2O4 nanoparticle composite material approach.

[0081] (1) Synthesis of graphene oxide GO.

[0082] (2) GO / Cu 1-x Sr x Synthesis of Cr2O4 / graphene oxide GO nanocomposites.

[0083] An embodiment of the present invention provides a method for synthesizing graphene oxide (GO).

[0084] First, 3 g of graphite powder, 23 ml of nitric acid, and 46 ml of concentrated sulfuric acid were mixed to synthesize graphene oxide GO; the mixture was stirred at room temperature for 40 minutes.

[0085] In an ice bath at 5°C, 9 g of potassium permanganate was added dropwise over 60 minutes while stirring continuously; the temperature was maintained at 38°C, stirring was continued for one hour, and 200 ml of deionized water was added dropwise; after the temperature was raised to 98°C, 30 ml of 35% concentration of hydrogen peroxide H2O2 was added, and the mixture turned bright yellow the next day; using a vacuum filtration device for cleaning, a solution of 200 ml of deionized water and 16.6 ml of concentrated hydrochloric acid was prepared until a neutral pH value was reached; after two hours of ultrasonic treatment, the produced GO was collected in a slurry form by centrifugation at a speed of 12,000 rpm for 40 minutes.

[0086] Finally, they were dried in vacuum at 60 °C for 48 h and then ground into homogeneous powder for further characterization.

[0087] GO / Cu provided in the embodiment of the present invention 1-x Sr x Synthesis method of Cr2O4 / graphene oxide GO nanocomposites.

[0088] 1 g of graphene oxide and 3 g of GO / Cu 1-x Sr x Cr2O4 / GO was dispersed in a mixed solution of 40 ml acetic acid and 20 ml ethylene glycol, and then ultrasonically treated at 60 °C for 1 h. The obtained GO and GO / Cu 1-x Sr x The mixture of Cr2O4 nanoparticles was sonicated for 15 min at a ratio of 1:1 and then magnetically stirred at 85 °C for 1 h; after the mixture was cooled, it was washed several times with deionized water until neutral by centrifugation at 3000 rpm for 15 min and finally dried in a vacuum oven at 60 °C overnight.

[0089] The embodiment of the present invention provides a method for measuring maximum specific capacitance in a three-electrode configuration system.

[0090] 1) X-ray diffraction analysis.

[0091] 2) Scanning electron microscopy.

[0092] 3) Optical analysis.

[0093] 4) Electrochemical measurements.

[0094] An embodiment of the present invention provides an X-ray diffraction analysis.

[0095] Powder X-ray diffraction (XRD) technology was used to determine the properties of graphene oxide GO, CuCr2O4 and GO / Cu 1-x Sr x Percent crystallinity, d-spacing, crystal structure, lattice constant, surface area, and grain size of Cr2O4 / graphene oxide nanocomposites.

[0096] like Figure 2 As shown, a GO / Cu 1-x Sr x Cr2O4 nanocomposites in high performance supercapacitor energy storage analysis system includes:

[0097] Precipitation module for the synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites.

[0098] Calcination module, used to calcine at 70°C for 2 hours to develop a high-performance supercapacitor nanoelectrode material.

[0099] Measurement module for measuring the maximum specific capacitance in a three-electrode configuration system showing the incorporation of GO / Cu on graphene sheets 1-x Sr x Capacitance properties of Cr2O4.

[0100] Another object of the present invention is to provide a computer device, the computer device comprising a memory and a processor, the memory storing a computer program, and when the computer program is executed by the processor, the processor executes the GO / Cu 1-x Sr x Steps in the analytical method for Cr2O4 nanocomposites for energy storage in high performance supercapacitors.

[0101] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, wherein when the computer program is executed by a processor, the processor executes the GO / Cu 1-x Sr x Steps in the analytical method for Cr2O4 nanocomposites for energy storage in high performance supercapacitors.

[0102] Another object of the present invention is to provide an information data processing terminal, the information data processing terminal is used to implement the GO / Cu 1-x Sr x Analysis of Cr2O4 nanocomposites in high performance supercapacitor energy storage systems.

[0103] During the synthesis process, it is crucial to select high-purity compounds. These compounds include Cr(NO3)3·9H2O (99%), Sr(NO3)2·6H2O (99%), C6H8O7 (99%), NH4OH (99.9%), as well as graphite powder, KMnO4 (99.9%), HNO3 (99.9%), H2SO4 (99.99%), H2O2, HCl and deionized water, all purchased from SigmaAldrich. These compounds do not require additional purification steps and can be used directly as is.

[0104] 1.1 Graphene oxide (GO) synthesis.

[0105] First, 3 g of graphite powder, 23 ml of nitric acid and 46 ml of concentrated sulfuric acid were mixed for the synthesis of graphene oxide (GO). This mixture was stirred at room temperature for 40 minutes. Next, 9 g of potassium permanganate was added dropwise for 60 minutes in an ice bath at 5°C while stirring continuously. After that, the temperature was maintained at 38°C, stirring was continued for one hour, and 200 ml of deionized water was added dropwise. After the temperature was raised to 98°C, 30 ml of 35% concentration of hydrogen peroxide (H2O2) was added, and the mixture turned bright yellow the next day. For cleaning using a vacuum filtration device, a solution of 200 ml of deionized water and 16.6 ml of concentrated hydrochloric acid was prepared until a neutral pH value was reached. After two hours of ultrasonic treatment, the produced GO was collected in a slurry form by centrifugation at a speed of 12,000 rpm for 40 minutes. Finally, it was dried in a vacuum at 60°C for 48 hours and then ground into a uniform powder for further characterization.

[0106] 1.2GO / Cu 1-x Sr x Synthesis of Cr2O4 / graphene oxide (GO) nanocomposites.

[0107] In order to synthesize GO / Cu 1-x Sr x Cr2O4 nanocomposite, 1g of graphene oxide and 3g of GO / Cu 1- x Sr x Cr2O4 was dispersed in a mixed solution of 40 ml acetic acid and 20 ml ethylene glycol. Then it was ultrasonically treated at 60 °C for 1 h. The obtained GO and GO / Cu 1-x Sr x The mixture of Cr2O4 nanoparticles was sonicated for 15 min at a ratio of 1:1 and then magnetically stirred for 1 h at 85 °C. After the mixture was cooled, it was washed several times with deionized water until neutral by centrifugation at 3000 rpm for 15 min and finally dried in a vacuum oven at 60 °C overnight.

[0108] 2.1 X-ray diffraction analysis.

[0109] Powder X-ray diffraction (XRD) technique was used to determine the carbonylation of graphene oxide (GO), CuCr2O4 and GO / Cu 1- x Sr x Percent crystallinity, d-spacing, crystal structure, lattice constant, surface area, and grain size of Cr2O4 / graphene oxide nanocomposites. The crystal structure of the synthesized materials was examined using X-ray diffraction technique, e.g. Figure 3 shown. Figure 3Part (a) shows a peak of (001) crystal plane at 2θ value of 11.6°, indicating that graphite is oxidized to graphene, which conforms to JCPDS7520 standard. The d spacing value becomes The XRD pattern of CuCr2O4 matches ICSD reference number 000340424, confirming the formation of a tetragonal crystal structure with lattice parameters of and (See Figure 3 (Part b) GO / Cu 1-x Sr x The characteristic peaks of Cr2O4 / graphene oxide nanocomposites appear at 2θ=10.90, 31.80, 38.50, 44.60, 49.10, 65.20 and 72.60, among which the (001) crystal plane shows the presence of graphene oxide. These low-intensity peaks shift to lower angles. In addition, the (220), (511) and (420) crystal planes represent the peaks of chromium copper oxide, proving that the crystallinity of the nanoparticles is maintained by the spin-coated layer, with The d-spacing value of .

[0110] 2.2 Scanning electron microscopy (SEM).

[0111] The surface morphology and microstructure of all samples were investigated using a NovaNano SEM 450 scanning electron microscope. Figure 4 (a) Part to Figure 4 Part (c) shows GO, Cu and GO / Cu 1-x Sr x SEM image of Cr2O4 chromate. Figure 4 As shown in part (a), GO particles exhibit random shapes and sizes, and the average particle size is determined to be 30 nm using ImageJ software. 1-x Sr x The average particle sizes of Cr2O4 are 25 nm and 27.4 nm, respectively. SEM images were captured in secondary electron mode to improve surface morphology resolution. The images show that all samples are highly porous. Figure 4 Part (a) shows the sheet-like layered structure of graphene oxide (GO) with a maximum thickness of about 1.1 nm and no bending at the edges, indicating the presence of oxygen functional groups and a stable morphology. Figure 4 Part (b) shows CuCr2O4, Figure 4 Part (c) shows the GO / Cu 1-x Sr x The alignment of Cr2O4 nanoparticles within the GO sheets covers the entire GO surface. This integration leads to particle agglomeration and disrupts the alignment of the graphene layers. GO / Cu 1-xSr x The non-uniform distribution of Cr2O4 nanoparticles on GO sheets is due to different composition ratios, forming spherical nanoparticles with an average particle size of 27.4 nm, calculated using Images software. These SEM images provide valuable insights into the structural features and arrangement of the synthesized nanomaterials.

[0112] Synthetic nanocomposites are based on the elemental composition of nanomaterials in Figure 5 The qualitative composition analysis showed the presence of copper, chromium, strontium, carbon and oxygen. In particular, the carbon peak appeared clearly in the spectrum, indicating that the carbon peak was formed in the GO / Cu 1- x Sr x Cr2O4 nanocomposites in the presence of graphene oxide. These elemental insights provide valuable information about the composition and purity of the synthesized nanomaterials.

[0113] 2.3. Optical analysis (Raman and PL spectroscopy).

[0114] like Figure 6 , GO / Cu 1-x Sr x The breathing mode (D band) of Cr2O4 shows a Raman shift similar to that of graphene oxide, indicating the interaction between silver nanoparticles and graphene oxide sheets through van der Waals and covalent bonding mechanisms. These interactions may lead to the shift in the position of the D peak. In addition, there is a direct proportional relationship between the number of defects in the graphene oxide structure and the intensity of the D band. GO / Cu 1-x Sr x Cr2O4 has a larger ID / IG ratio (1.57) than that of GO (1.01), indicating that there are more defect sites in this material. In terms of the G band, the removal of oxygen-containing functional groups does not change the stretching mode of C=C, which means that in graphene oxide, oxygen is mainly present at the edges and other defect sites. Therefore, graphene oxide maintains a structure similar to that of few-layer graphene, and the oxidation and reduction processes occur at defect sites. In addition, there is an inverse relationship between the ID / IG ratio and the sp2 domain size. Therefore, according to Eq. 2, GO / Cu 1-x Sr x The grain size of Cr2O4 / graphene oxide (12 nm) is smaller than that of GO (19 nm). This smaller grain size and higher ID / IG ratio indicate that the reduction process increases the edge number density, which may lead to more graphene oxide separation or breakage. The reduced grain size and more defect sites act as nucleation sites, promoting additional GO / Cu 1-x Sr x Cr2O4 is anchored on the graphene oxide surface.

[0115] 2.4. Electrochemical measurements.

[0116] 2.4.1. Electrochemical impedance spectroscopy (EIS).

[0117] like Figure 7 , the electron transport capability of the synthesized nanomaterials was investigated using the electrochemical impedance spectroscopy (EIS) technique. The changes in the electrode structure mainly affected parameters such as Rct (charge transfer resistance) and CPE (constant phase element), which can be attributed to the conductive nature of the material. Both capacitance and surface roughness contribute to the properties of CPE, and the values ​​of the surface roughness factor (α) are between 0.75, showing a relatively reasonable surface roughness, such as Figure 8 GO (b), CuCr2O4 (c) and GO / Cu 1- x Sr x Nyquist plot of Cr2O4 nanocomposite and its fitting model. According to the relationship kapp = RT / F2, the calculated values ​​of Rct are 1.82Ω, 1.42Ω and 1.29Ω, respectively, and the corresponding kapp values ​​are 1.65×10 7 cm2s 1 , 1.85×10 7 cm2s 1 and 3.01×10 7 cm2s 1 In 1 M KOH solution, the minimum Rct corresponds to the maximum conductivity, as shown in the case where the semicircles represent high frequencies, indicating that due to the 1-x Sr x The integration of Cr2O4 nanoparticles into the GO structure leads to the maximum electrolytic activity. For 1M KOH electrolyte solution, the relative ease of electron transport leads to the maximum energy storage capacity, which is a prerequisite for high-performance supercapacitor electrodes. It is clear from the Nyquist plot that the semicircles correspond to high powers associated with the charge transfer resistance (Rct). The ions have always appeared as straight lines in the low-frequency range, indicating that the diffusion of hydroxyl ions within the electrode material leads to the Warburg impedance (W).

[0118] 2.4.2. Cyclic voltammetry (CV) analysis.

[0119] The redox behavior can be observed by plotting the current response versus potential gradient for different values ​​through cyclic voltammetry analysis. This analysis allows the study of chemical reactions initiated by electron transfer in 1 M KOH electrolyte solution by forward and reverse scanning, such as Fig. 9The increase in scan rate causes the reduction peak to shift to more negative potentials and the oxidation peak to shift to more positive potentials, confirming the dominance of the redox process, thus supporting charge storage.

[0120] Where I is the voltammeter current, V is the potential window, m is the mass of the electrode (grams), v is the scan rate (mV / s), and the integral part is the area under the curve. At the maximum scan rate, the maximum specific capacitance indicates the difficulty of electrolyte ions to penetrate the interior of the electrode. The diffusion coefficient values ​​in alkaline and acidic solutions can be estimated using the RandlesSevick plot using Ip (peak current) and the square of the scan rate. The linear relationship of the diffusion-controlled mechanism is supported on the inner surface of the electrode. Obviously, the lower Rct accompanied by larger Kapp and diffusion coefficient values ​​indicates greater reaction feasibility, indicating an increase in the enhanced specific capacitance value of 1935.8F / g in 1M KOH electrolyte solution. The proposed supercapacitor nanoelectrode material supports the maximum energy storage capacity, endorsing the surface redox reaction with the specific capacity of the reported material.

[0121] 2.4.3.GCD.

[0122] The oxidation and reduction peaks that appear in the CV curves can be attributed to the nonlinear behavior of the GCD curves during the charge and discharge process, clearly showing the redox active nature of the material. As the current density increases, the discharge current decreases. The specific capacity (Q) can be calculated from the GCD data using equation (1), where I represents the charge / discharge current, represents the charge / discharge time (seconds), and m represents the mass of the deposited material.

[0123]

[0124] Capacitance expresses the total charge that a capacitor can store or release during a complete charge and discharge cycle. Fig.10 (a) and Fig.10 (b) shows the charge / discharge capacity at different current densities (from 0.5 to 9 A g^-1). Clearly, both electrolytes maintain good capacity values ​​even when the current is increased eightfold. The symmetrical charge / discharge curves indicate strong electrochemical reversibility.

[0125]

[0126]

[0127] The maximum power density increases with the discharge time (td) from 105.92 to 278.9 kW / kg. In contrast, the energy density decreases from 47.98 to 22.85 kWh / kg. These results indicate that the GO / Cu based 1-x Sr xCr2O4 electrode materials are very suitable for energy storage applications such as supercapacitors.

[0128] In order to prove the creativity and technical value of the technical solution of the present invention, the following is provided: 1-x Sr x Example of application of Cr2O4 nanocomposite materials in high performance supercapacitors.

[0129] Example 1: GO / Cu 1-x Sr x Synthesis of Cr2O4 nanocomposites.

[0130] 1. Synthesis of graphene oxide (GO).

[0131] 3 g of graphite powder, 23 ml of nitric acid and 46 ml of concentrated sulfuric acid were mixed and stirred at room temperature for 40 minutes.

[0132] In an ice bath at 5°C, 9 g of potassium permanganate was slowly added and stirred for 60 min. The temperature was maintained at 38°C and stirring was continued for 1 h. 200 ml of deionized water was added dropwise.

[0133] The temperature was raised to 98°C, 30 ml of 35% strength hydrogen peroxide (H2O2) was added, and the mixture turned bright yellow.

[0134] The solution was cleaned using a vacuum filtration apparatus until a neutral pH was reached, and after sonication for 2 h, the GO slurry was collected by centrifugation (12,000 rpm, 40 min).

[0135] The resulting product was dried in vacuum at 60 °C for 48 h and ground into a homogeneous powder for further characterization.

[0136] 2. GO / Cu 1-x Sr x Synthesis of Cr2O4 nanocomposites.

[0137] 1 g GO and 3 g GO / Cu 1-x Sr x Cr2O4 was dispersed in a mixed solution of 40 ml acetic acid and 20 ml ethylene glycol and treated with ultrasound at 60 °C for 1 h.

[0138] The obtained GO and GO / Cu 1-x Sr x The mixture of Cr2O4 was sonicated at a 1:1 ratio for 15 min and then magnetically stirred at 85 °C for 1 h.

[0139] After the mixture was cooled, it was centrifuged at 3000 rpm for 15 min, washed with deionized water until neutral, and finally dried in a vacuum oven at 60 °C overnight.

[0140] Example 2: Preparation and performance testing of high-performance supercapacitor electrodes.

[0141] 1. Preparation of electrodes.

[0142] The synthesized GO / Cu 1-x Sr x The Cr2O4 nanocomposite material was mixed with conductive carbon black and polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1 to prepare a slurry.

[0143] The slurry was coated on a nickel foam substrate, dried and pressed to obtain a supercapacitor electrode.

[0144] 2. Electrochemical performance test.

[0145] The specific capacitance of the electrode was measured using a three-electrode configuration system, with GO / Cu as the working electrode. 1-x Sr x Cr2O4 nanocomposite electrode, the reference electrode is saturated calomel electrode (SCE), and the counter electrode is platinum sheet.

[0146] Cyclic voltammetry (CV) tests were carried out in 1M KOH electrolyte with a scan rate of 3mV / s. The results showed that the maximum specific capacitance reached 1935.8F / g, which was significantly higher than GO used alone (480.190F / g).

[0147] Electrochemical impedance spectroscopy (EIS) analysis showed that GO / Cu 1-x Sr x The charge transfer resistance (Rct) of the Cr2O4 nanocomposite is 1.29Ω, indicating its higher electrical conductivity.

[0148] After 10,000 charge-discharge cycles, the specific capacitance retention of the electrode exceeded 90%, showing excellent cycling stability.

[0149] From the above examples, it can be seen that GO / Cu 1-x Sr x The application of Cr2O4 nanocomposite materials in high-performance supercapacitors demonstrates its remarkable electrochemical performance and stability, verifying the creativity and technical value of the technical solution of the present invention. This technical solution not only improves the energy storage efficiency of supercapacitors, but also reduces production costs, meets the requirements of green environmental protection, and has broad market application prospects.

[0150] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A GO / Cu 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The following steps are involved: Step 1: Synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites; Step 2, calcining at 70° C. for 2 hours to generate a high-performance supercapacitor nanoelectrode material; Step 3, the maximum specific capacitance is measured in a three-electrode configuration system, showing that the GO / Cu 1-x Sr x Capacitance properties of Cr2O4.

2. GO / Cu as claimed in claim 1 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The GO / Cu was synthesized by precipitation method. 1-x Sr x Cr2O4 Nanoparticle Composite Method: (1) Synthesis of graphene oxide GO; (2) GO / Cu 1-x Sr x Synthesis of Cr2O4 / graphene oxide GO nanocomposites.

3. GO / Cu as claimed in claim 2 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The graphene oxide GO synthesis method: First, 3 grams of graphite powder, 23 milliliters of nitric acid and 46 milliliters of concentrated sulfuric acid were mixed to synthesize graphene oxide GO; the mixture was stirred at room temperature for 40 minutes; In an ice bath at 5°C, 9 g of potassium permanganate was added dropwise over 60 minutes while stirring continuously; the temperature was maintained at 38°C, stirring was continued for one hour, and 200 ml of deionized water was added dropwise; after the temperature was raised to 98°C, 30 ml of 35% concentration of hydrogen peroxide H2O2 was added, and the mixture turned bright yellow the next day; using a vacuum filtration device for cleaning, a solution of 200 ml of deionized water and 16.6 ml of concentrated hydrochloric acid was prepared until a neutral pH value was reached; after two hours of ultrasonic treatment, the produced GO was collected in a slurry form by centrifugation at a speed of 12,000 rpm for 40 minutes; Finally, they were dried in vacuum at 60 °C for 48 h and then ground into homogeneous powder for further characterization.

4. GO / Cu as claimed in claim 2 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The GO / Cu 1-x Sr x Synthesis method of Cr2O4 / graphene oxide GO nanocomposite materials: 1 g of graphene oxide and 3 g of GO / Cu 1-x Sr x Cr2O4 was dispersed in a mixed solution of 40 ml acetic acid and 20 ml ethylene glycol; then ultrasonically treated at 60 °C for 1 h; the obtained GO and GO / Cu 1-x Sr x The mixture of Cr2O4 nanoparticles was sonicated for 15 min at a ratio of 1:1 and then magnetically stirred at 85 °C for 1 h; after the mixture was cooled, it was washed several times with deionized water until neutral by centrifugation at 3000 rpm for 15 min and finally dried in a vacuum oven at 60 °C overnight.

5. GO / Cu as claimed in claim 2 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The maximum specific capacitance is measured in a three-electrode configuration system: 1) X-ray diffraction analysis; 2) Scanning electron microscopy; 3) Optical analysis; 4) Electrochemical measurements.

6. GO / Cu as claimed in claim 1 1-x Sr x Cr2O4 nanocomposite materials for energy storage analysis in high performance supercapacitors, characterized in that: The X-ray diffraction analysis: Powder X-ray diffraction (XRD) technology was used to determine the properties of graphene oxide GO, CuCr2O4 and GO / Cu 1-x Sr x Percent crystallinity, d-spacing, crystal structure, lattice constant, surface area, and grain size of Cr2O4 / graphene oxide nanocomposites.

7. A method for implementing the GO / Cu as claimed in any one of claims 1 to 6 1-x Sr x The analytical system of Cr2O4 nanocomposite materials in high performance supercapacitor energy storage analytical method is characterized in that: GO / Cu 1-x Sr x Cr2O4 nanocomposites in high performance supercapacitor energy storage analysis system includes: Precipitation module for the synthesis of GO / Cu by precipitation method 1-x Sr x Cr2O4 nanoparticle composites; Calcination module, used to develop a high-performance supercapacitor nanoelectrode material by calcining at 70°C for 2 hours; Measurement module for measuring the maximum specific capacitance in a three-electrode configuration system showing the incorporation of GO / Cu on graphene sheets 1- x Sr x Capacitance properties of Cr2O4.